Análise termodinâmica das reações de reforma do metano e do GLP para a produção de hidrogênio - Franco, Tatiana Vilarinho (2009)
The chemical equilibrium compositions of steam and dry methane reforming reactions, (SMR) and (DMR), respectively, are calculated by two distinct methods: (1) evaluation of the equilibrium constants; (2) Lagrange multipliers. The chemical equilibrium compositions of LPG steam reforming reaction are calculated by the method of evaluation of equilibrium constants. Both methods result in systems of non-linear algebraic equations, solved numerically using the open-source software Scilab © INRIA-ENPC. The main contribution of this study is, therefore, to conduct a comparative thermodynamic analysis for these reactions, determining the influence of key operational variables on chemical equilibrium. Effects of temperature, pressure, initial H2O/CH4 ratio (steam methane reforming), initial CH4:CO2:N2 ratio (dry methane reforming) and C3H8:C4H10:H2O ratio (steam reforming of LPG) on the reaction products are evaluated. For the steam methane reforming, the equilibrium compositions were calculated as a function of temperature and pressure, H2 yield and H2/CO selectivity, both as a function of temperature, CH4 conversion and carbon deposition, as function of the initial ratio H2O/CH4. For the dry methane reforming, the equilibrium compositions, H2 yield, H2/CO selectivity, H2/CO2 selectivity and CH4 conversion were calculated as a function of temperature. Also, the equilibrium constants for the reactions considered in the steam reforming process of LPG were evaluated as a temperature function. For results validation, two procedures are employed: (1) comparison between experimental data and simulated equilibrium data, published in the literature; (2) calculation of the intrinsic reaction rates, which should be equal to zero at equilibrium conditions.